Neutrophil-Lymphocyte Ratio, prognostic nutritional index and CRP - Albumin Ratio significantly predict mortality in ICU patients with low nutrition risk. - Wullur, Yulia; Taslim, Nurpudji Astuti (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction and Methods: This observational retrospective cohort study was conducted in the ICU of Wahidin Sudirohusodo Hospital, Indonesia, from April 2022 to March 2023. All patients admitted to the ICU during the study period were considered. Data collected from medical records included patient demographics, clinical characteristics, prognostic indicators, and outcomes. Bivariate and multivariate regression analysis was used to evaluate the associations between prognostic indicators and mortality both in low-risk and high-risk subgroup. The results were presented as hazard ratios (HRs) with 95% confidence intervals (CIs). To predict accuracy of prognostic biomarker, Receiver Operating Characteristic (ROC) curve analysis was conducted. The area under the ROC curve (AUC) was calculated to evaluate the discriminative ability of each biomarker Result: In a study of 1,106 ICU patients. The length of stay in the ICU and hospital for survivors is shorter than for non-survivors. Hazard ratio analysis showed that higher PNI significantly reduced the risk of death (unadjusted HR 0.914, adjusted HR 0.910), whereas higher CAR and NLR were associated with increased risk of death (CAR unadjusted HR 1.020, adjusted HR 1.017; unadjusted NLR HR 1.018, adjusted HR 1.014 ). This effect was less pronounced in patients at high nutritional risk, with nonsignificant HR values. ROC curve analysis showed that CRP/Albumin (AUC: 0.696), NLR (AUC: 0.575), and PNI (AUC: 0.325). Conclusion: NLR, PNI, and CAR are valuable prognostic indicators in ICU settings, providing crucial information on mortality risk especially in patients with low nutritional risk. The data supports their use in clinical assessments to tailor interventions that address inflammation and nutritional deficits